2019
DOI: 10.1002/phar.2296
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Oral versus Continued Intravenous Antibiotics for Patients with Pyogenic Liver Abscesses: A Retrospective Analysis

Abstract: Introduction The management of pyogenic liver abscesses usually requires 4 weeks of antibiotic therapy. It is unknown if oral (PO) antibiotics are as effective as intravenous (IV) antibiotics for this indication. Objectives To compare 30‐, 60‐, and 90‐day readmission rates between patients with pyogenic liver abscesses receiving IV antibiotics for the duration of therapy and those who were transitioned to PO antibiotics after discharge from the hospital. Methods This retrospective study included patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The American Society of Infectious Diseases recommends intravenous antibiotics as first-line therapies for complicated intraabdominal infections [13]. The duration of therapy with intravenous antibiotics for patients with pyogenic liver abscess is generally 2-3 weeks, followed by 1-2 months of oral therapy [14,15]. The size of the liver abscess is usually used to determine whether image-guided needle aspiration, percutaneous catheter drainage, or surgical drainage should be performed.…”
Section: Introductionmentioning
confidence: 99%
“…The American Society of Infectious Diseases recommends intravenous antibiotics as first-line therapies for complicated intraabdominal infections [13]. The duration of therapy with intravenous antibiotics for patients with pyogenic liver abscess is generally 2-3 weeks, followed by 1-2 months of oral therapy [14,15]. The size of the liver abscess is usually used to determine whether image-guided needle aspiration, percutaneous catheter drainage, or surgical drainage should be performed.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis done by Giangiuli et al demonstrated higher 30-day admission rates in patients who were transitioned to oral antibiotics, mostly quinolones, at time of discharge as compared to IV antibiotics, mostly beta-lactams, in PLA [7]. Mohan et al demonstrated sevenfold higher risk or colorectal cancer in patients with cryptogenic PLA.…”
Section: Discussionmentioning
confidence: 99%
“…According to the present study 2-3 weeks of oral antimicrobial therapy with or without percutaneous drainage/aspiration was adequate for the treatment of uncomplicated liver abscess. Further studies comparing the efficacy of empirical oral and intravenous antimicrobial for the treatment of liver abscess 20 , in a retrospective study of pyogenic liver abscess observed that, 30-day readmission rate was significantly higher in patients who received transition to oral (IV followed by oral) antibiotics (39.6% Vs 17.6%) than continued IV antibiotics. Whereas in present study overall only 5 participants required readmission, 3 participants had accidental slippage of PCD, 1 participant had new onset shock and 1 had new abscess formation.…”
Section: Outcomementioning
confidence: 99%